2019
DOI: 10.1186/s12879-019-4687-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of GeneXpert MTB/RIF system performances in the diagnosis of extrapulmonary tuberculosis

Abstract: BackgroundTuberculosis represents a serious public health problem and a significant diagnostic and therapeutic challenge worldwide. Molecular diagnostic techniques are crucial in the World Health Organization’s new tuberculosis control strategy.This study aims to evaluate the performance of GeneXpert MTB/RIF (Cepheid Sunnyvale, CA, United States) in diagnosis of extra-pulmonary tuberculosis then compare it’s performance in detecting Rifampicin resistance to GenoType MTBDRplus (HAIN Life Sciences, Nehren, Germa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 23 publications
4
41
1
4
Order By: Relevance
“…In our study, we noted the detection rate of 26.3% for biopsy specimens diagnosed with TB on routine histopathology. A study including 714 cases of pulmonary and extra-pulmonary TB samples concluded that the detection rates of MTB by GeneXpert assay were 23.85% and 18.41%, respectively, for pulmonary and extra-pulmonary samples [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we noted the detection rate of 26.3% for biopsy specimens diagnosed with TB on routine histopathology. A study including 714 cases of pulmonary and extra-pulmonary TB samples concluded that the detection rates of MTB by GeneXpert assay were 23.85% and 18.41%, respectively, for pulmonary and extra-pulmonary samples [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of EPTB remains challenging for both the clinicians and microbiologists. Nevertheless, the difficulty to gain access to specific sampling sites results in paucibacillary samples and reduces the sensitivity of conventional diagnostic tools [3].…”
Section: Introductionmentioning
confidence: 99%
“…GeneXpert is recommended by the World Health Organization in the pulmonary and extra-pulmonary tuberculosis diagnosis in both immunocompetent and immunocompromised patients [8,9]. It is a rapid molecular test with high performance (sensitivity and specificity) [10].…”
Section: Discussionmentioning
confidence: 99%